2017
DOI: 10.18063/jsc.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Policy-aware assessment of environmental impacts from transport in smart cities

Abstract: Abstract:In recent research a performance evaluation framework for traffic management and Intelligent Transport Systems was developed, consisting of a set of Key Performance Indicators (KPIs) for the themes of traffic efficiency, safety, pollution reduction and social inclusion, all of which are key components of a smart city. One of the innovative elements of these KPIs is their ability to consider the transport policy layer, in the sense that the evaluation of the suitability and effectiveness of different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…For instance, in the case of Brussels, previous work by the authors (Kaparias et al, 2016) has found that, despite great benefits in terms of the mobility efficiency of public transport passengers, the immediate introduction of the public transport priority system will inevitably have a negative short-term effect on pollution, mainly due to the reduction of the green time for car traffic. This will be likely gradually mitigated by changes in route and mode choice, but as is commonly the case with the procurement procedures of such schemes, resources to estimate such effects that are beyond the direct goal of the scheme (i.e.…”
Section: Results In a Broader Policy-related Contextmentioning
confidence: 99%
See 3 more Smart Citations
“…For instance, in the case of Brussels, previous work by the authors (Kaparias et al, 2016) has found that, despite great benefits in terms of the mobility efficiency of public transport passengers, the immediate introduction of the public transport priority system will inevitably have a negative short-term effect on pollution, mainly due to the reduction of the green time for car traffic. This will be likely gradually mitigated by changes in route and mode choice, but as is commonly the case with the procurement procedures of such schemes, resources to estimate such effects that are beyond the direct goal of the scheme (i.e.…”
Section: Results In a Broader Policy-related Contextmentioning
confidence: 99%
“…The outcome has been a predictive evaluation tool for road traffic management and ITS, called CONDUITS_DST, in which two of the four KPI categories have been integrated to date: the pollution generated by the various transport modes in the form of emissions of both global and local pollutants, and the traffic efficiency, expressed through measures such as travel time and network reliability. Preliminary testing of the tool in three European cities (Brussels, Stuttgart and Tel Aviv) using existing microscopic traffic simulation models has, again, confirmed the validity of the methodology and has demonstrated the viability, usefulness and timeliness of the approach (Eden et al, 2012;Eden et al, 2013;Kaparias et al, 2016).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations